Situated Learning and the Development of Relationships: Bridging the Gap between Veterinarians and Researchers - Tiffany Whitcomb; Edward Taylor (Adult Education Research Conference, 2014)
The development of the student teacher relationship has been largely ignored within the tenets of situated learning. Here we report the results of a mixed method study that explored relationships between researchers and veterinarians in a biomedical techniques training program designed theoretically and practically from the lens of situated learning.